2020
DOI: 10.4103/ijnmr.ijnmr_112_19
|View full text |Cite
|
Sign up to set email alerts
|

Compassion satisfaction and fatigue in cardiovascular nurses: A cross-sectional descriptive study

Abstract: Background: Cardiovascular nurses play a key role in improving the treatment outcomes in patients. Compassion satisfaction and fatigue influence the quality of nursing care. Thus, it is important to examine the levels of compassion satisfaction and fatigue in cardiovascular nurses. This study was performed to determine compassion satisfaction and fatigue in cardiovascular nurses. Materials and Methods: This cross-sectional, descriptive study was conducted with a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
(30 reference statements)
2
12
0
3
Order By: Relevance
“…41 It has been reported that most emergency nurses experience compassion fatigue and nurses working in surgical units experience moderate burnout and secondary traumatic stress. 42,43 Barmawi et al 44 determined that intensive care nurses experienced compassion fatigue and use both mental and physical avoidance at and outside of work as a coping mechanism and that they needed counseling or motivation to address this. In a study conducted in the current pandemic, health workers in COVID-19 units and emergency departments were found to have higher levels of compassion fatigue than those in other units.…”
Section: Discussionmentioning
confidence: 99%
“…41 It has been reported that most emergency nurses experience compassion fatigue and nurses working in surgical units experience moderate burnout and secondary traumatic stress. 42,43 Barmawi et al 44 determined that intensive care nurses experienced compassion fatigue and use both mental and physical avoidance at and outside of work as a coping mechanism and that they needed counseling or motivation to address this. In a study conducted in the current pandemic, health workers in COVID-19 units and emergency departments were found to have higher levels of compassion fatigue than those in other units.…”
Section: Discussionmentioning
confidence: 99%
“…Istichomah, I, Et Al 245 menunjukkan bahwa tidak ada hubungan yang signifikan antara usia perawat, tingkat pendidikan, pengalaman kerja, dan jam kerja bulanan dan skor kepuasan, burnout, dan STS (secondary traumatic stress), dan skor kelelahan, Pengalaman kerja berhubungan dengan skor STS (r = 0.18, p = 0.01). Namun, tidak ada hubungan yang signifikan dengan kepuasan dan kelelahan (p> 0,05) [17].…”
Section: Hasil Dan Pembahasanunclassified
“…Penelitian lain menunjukkan pengalaman kerja yang lebih tinggi pada perawat menyebabkan peningkatan kelelahan dan kepuasan [17].…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…[ 17 ] In fact, the self-compassionate approach helps patients better cope with uncontrolled chronic stress[ 18 ] and leads to a sense of self-care and awareness and creates a non-judgmental attitude toward one's failures. [ 15 19 ] Research in health fields have noted the mediating and supporting role of self-compassion in relation to psychological distress. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%